HUBUNGAN MEMBACA CEPAT MENGGUNAKAN STRATEGI POLA PENALARAN DENGAN KEMAMPUAN MENENTUKAN IDE POKOK PARAGRAF ARGUMENTASI SISWA SMA RIZKI ANANDA - Ramadianti Lubis, Alfitriana Purba (EDUCATE, 2025)
The research objective is to develop students' speed reading skills using reasoning pattern strategies, which will help them determine the main idea of argumentative paragraphs. The research method used was descriptive research using moment correlational statistical analysis. The sample for this study was one class, consisting of 25 students in total. Based on the results of the study on "The Relationship Between Speed Reading Using Reasoning Pattern Strategies and the Ability to Determine the Main Idea of Argumentative Paragraphs by Grade 10 Students of Rizki Ananda Senior High School in the 2020-2021 Academic Year," several conclusions were obtained. Speed reading using reasoning pattern strategies and the ability to determine the main idea of argumentative paragraphs by Grade 10 students of Rizki Ananda Senior High School in the 2020-2021 Academic Year was categorized as Poor, based on an average score of 42.8. Speed reading using reasoning pattern strategies and the ability to determine the main idea of argumentative paragraphs by Grade 10 students of Rizki Ananda Senior High School in the 2020-2021 Academic Year was categorized as Good, based on an average score of 74.2.